Experimentation d 'une approche parallele en calcul des structures - Cognard, Jean-Yves; Dureisseix, David; Ladeveze, Pierre; Lorong, Philippe (European Journal of Computational Mechanics, 1996)
We describe the headlines of a mechanical formulation that inforce a « parallel » approach for structural analysis in small pertubations, restricted here to linear elasticity. The description of the medium is an assembly of substructures and interfaces. Liaisons and contacts between substructures are treated by the interfaces which possess their own behaviour. Convergence is proved under classical stability assumptions. Several exemples figure out the behaviour of the propounded approach on parallel architecture computers.